1990
DOI: 10.1002/1097-0142(19900215)65:4<958::aid-cncr2820650423>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines in colorectal cancer. Evaluation of polyamine concentrations in the colon tissue, serum, and urine of 50 patients with colorectal cancer

Abstract: Total, free, and acetylated polyamine concentrations were measured simultaneously in colon tissue, serum, and urine of 50 patients with histologically proven colorectal cancer, 40 patients with nonmalignant gastrointestinal diseases, and 30 healthy volunteers. Compared with histologically unaffected colon tissue, concentrations were significantly (P less than 0.001) higher for putrescine, elevated for cadaverine, and nearly identical for spermidine and spermine in colon carcinoma, whereas N1-acetylated and N8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…A previous study indicated that the amount of polyamines excreted in the urine was higher in patients with cancer compared to that in healthy individuals (3). However, results of subsequent studies showed that the total amount, as well as the amount of individual free and monoacetylated polyamines in the urine, were not suitable as reliable tumor markers, as these yielded a number of false positive and negative results (4,5). N 1 ,N 12 -diacetylspermine (DiAcSpm) is a minor component of human urine that constitutes less than 0.5% of the total polyamine species in normal human urine.…”
Section: Introductionmentioning
confidence: 86%
“…A previous study indicated that the amount of polyamines excreted in the urine was higher in patients with cancer compared to that in healthy individuals (3). However, results of subsequent studies showed that the total amount, as well as the amount of individual free and monoacetylated polyamines in the urine, were not suitable as reliable tumor markers, as these yielded a number of false positive and negative results (4,5). N 1 ,N 12 -diacetylspermine (DiAcSpm) is a minor component of human urine that constitutes less than 0.5% of the total polyamine species in normal human urine.…”
Section: Introductionmentioning
confidence: 86%
“…This led to a great flurry of activity examining the possibility that polyamines in body fluids may be biological markers of malignancy (for reviews, see Janne et al 1978;Pegg, 1988). Unfortunately, as a marker, polyamines, particularly urinary polyamines, were nonspecific with false positives being observed in patients with gastrointestinal diseases (Loser et al 1990) and during pregnancy (Russell et al 1971).…”
Section: Cancermentioning
confidence: 99%
“…High polyamine levels have been detected in most types of cancers (7)(8)(9). In colorectal cancer, the polyamine contents are increased 3-to 4-fold over those found in the equivalent normal tissue (10,11). Depletion of the intracellular polyamine pools invariably inhibits cell growth.…”
Section: Introductionmentioning
confidence: 99%